"Gestión de la comunicación en situaciones de crisis: el caso Conga" - Lozano Rojas, Esther Elena (2020)
This academic work is an analysis of the corporate crisis of the mining company Yanacocha, whose key gold mining project, Conga, located in the Peruvian department of Cajamarca, was rejected by the local population since the beginning in 2010, and finally cancelled in October 2012. It is a communication analysis based on the news coverage of the events between October 2011 and October 2012, the most sensible period for the project. The coverage showed the company´s inappropriate responses to the crisis and how they damaged its corporate image. Using information from the local and national mass media, we review how the social conflict evolved, how it became also a political news story, until it bursted into a high-impact crisis that led to the closure of the Conga project. We examine Yanacocha´s handling of the crisis and observe the ineffective approach around a critical component in crisis management: crisis communication.